PENGEMBANGAN MEDIA JAM MANIPULATIF BERBASIS FUN LEARNING UNTUK MENINGKATKAN PEMAHAMAN MATEMATIKA SISWA KELAS II SEKOLAH DASAR - Veronicha Fernanda; Masrurotul Mahmudah; Nur Laili (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
This study was motivated by the low level of understanding among second-grade students at SD Negeri 1 Banarjoyo regarding time measurement material due to the use of conventional teaching methods and the lack of engaging and concrete learning media. This study aimed to develop a manipulative clock media based on fun learning and to determine its feasibility and effectiveness in improving students’ mathematical understanding. The research method used was Research and Development (R&D) with the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The subjects of this study were second-grade students of SD Negeri 1 Banarjoyo. Data collection techniques included observation, interviews, validation questionnaires, and learning outcome tests. The results showed that the developed media obtained a validation score of 3.80 from media experts and 3.72 from material experts, both categorized as highly valid. In addition, the media was declared effective based on the improvement in students’ learning outcomes, where the average pretest score of 65.20 increased to 84.01 in the posttest, with a learning mastery level reaching 80%. These results indicate that the manipulative clock media based on fun learning can help students understand time measurement concepts in a more concrete, interactive, and enjoyable way. Therefore, the developed media is feasible to be used as an innovative alternative in mathematics learning at the elementary school level. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya pemahaman siswa kelas II SD Negeri 1 Banarjoyo terhadap materi pengukuran waktu akibat penggunaan metode pembelajaran yang masih konvensional serta kurangnya media pembelajaran yang menarik dan konkret. Penelitian ini bertujuan untuk mengembangkan media jam manipulatif berbasis fun learning serta mengetahui kelayakan dan efektivitasnya dalam meningkatkan pemahaman matematika siswa. Metode penelitian yang digunakan adalah Research and Development (R&D) dengan model ADDIE yang meliputi tahap analysis, design, development, implementation, dan evaluation. Subjek penelitian adalah siswa kelas II SD Negeri 1 Banarjoyo. Teknik pengumpulan data dilakukan melalui observasi, wawancara, angket validasi, dan tes hasil belajar. Hasil penelitian menunjukkan bahwa media yang dikembangkan memperoleh skor validasi ahli media sebesar 3,80 dan validasi ahli materi sebesar 3,72 dengan kategori sangat valid. Selain itu, media dinyatakan efektif berdasarkan peningkatan hasil belajar siswa, yaitu nilai rata-rata pretest sebesar 65,20 meningkat menjadi 84,01 pada posttest dengan tingkat ketuntasan belajar mencapai 80%. Hasil tersebut menunjukkan bahwa media jam manipulatif berbasis fun learning mampu membantu siswa memahami konsep pengukuran waktu secara lebih konkret, interaktif, dan menyenangkan. Dengan demikian, media yang dikembangkan layak digunakan sebagai alternatif inovatif dalam pembelajaran matematika di sekolah dasar.